Робастифицированное бездатчиковое векторное управление асинхронным двигателем на основе адаптивного наблюдателя пониженного порядка - Пересада, С.М.; Ковбаса, С.Н.; Дымко, С.С. (Технічна електродинаміка, 2012)
A novel speed sensorless indirect field oriented control of induction motor is designed. Algorithm is based on reduced order adaptive speed observer and provides exponential tracking of smooth speed and flux reference signals under assumptions of unknown constant load torque. Proposed solution has improved robustness properties with respect to stator and rotor resistances perturbations. Results of simulations and experimental investigations are also presented.